Environmental impact of the most representative Spanish olive oil farming systems: a Life Cycle Assessment study - Fernández-Lobato, Lázuli; Ruiz-Carrasco, Beatriz; Tostado-Véliz, Marcos; Jurado, Francisco; Vera, David (Elsevier, 2024)
Agricultural production is an essential activity in the global economy that must advance towards the design of sustainability projects hand-in-hand with consumers, companies, and policymakers. An exhaustive study, in line with the guidelines set by government entities, is required to quantify this impact in an ample spectrum of environmental categories. Life Cycle Assessment (LCA) is a powerful tool that enables obtaining such information, as other authors have already demonstrated in different sectors. This study employs LCA to determine the environmental impact of virgin olive oil production, considering different agricultural and industrial production systems in Spain. For this purpose, a wide range of cultivated olive tree crops and different types of olive oil mill facilities in Andalusia have been studied-the territory of Spain with the highest dedication to olive oil production. This area has a strong emphasis on developing projects within this economic sector. The study focuses on olives, virgin olive oil and hectares of cultivation land, adopting a “cradle-to-gate” approach, and including economic allocation, considering the main processes related to its production in the agricultural and industrial phases. The study time covers the five most recent harvests (2017/18 to 2021/22) to obtain appropriate and updated environmental impact values. The results from the study time indicate that higher densification, irrigation, and slope crops lead to a higher environmental impact. Specifically, the climate change category of the functional unit ranges between 1.90 (low yield crops) and 6.09 kg of CO2 equivalent (super-intensive irrigated), while in the most representative cases, extensive crops, it results in 2.90 (rainfed) and 3.49 (irrigated) kg of CO2 equivalent. It should be noted that this study breaks new ground by thoroughly assessing the environmental impact of different olive oil production methods in Spain.
Keywords: Aceite de oliva -- Producción; Cambios climáticos; Impacto ambiental; Life cycle assessment; Environmental impact; Climate change; Olive oil production